DIVERSIFICATION OF LIVELIHOOD SOURCES OF THE SOUTHERN SLOPE OF MOUNT SLAMET COMMUNITY THROUGH RABBIT CULTIVATION: DIVERSIFIKASI SUMBER NAFKAH MASYARAKAT LERENG SELATAN GUNUNG SLAMET MELALUI EDUKASI BUDIDAYA KELINCI - Azka Thoriq Ash-shiddiqi; Pangky Suwito; Malinda Aptika Rachmah; Sunendar (Darmabakti Cendekia: Journal of Community Service and Engagements, 2024)
Background: Kemutug Lor Village is located on the slopes of Mount Slamet which has natural resource potential, but its people live below the poverty line. Rabbit farming is one alternative solution to diversify the income of the people of Kemutug Lor Village. Objective: This activity aims to transfer knowledge and skills through education on rabbit farming. Method: This activity used a participatory method from determining the problem's urgency, and selecting alternative strategies by utilizing local potential, and education/counseling activities. The participants were the Wana Karya Lestari LMDH and the Kemutug Lor village community. The tools and materials used are cameras, stationery, materials, and rabbits. Results: The participants actively discussed during the activity. The results of the pre-test and post-test showed that there was an increase in score post-test. So it can be said that after the counseling activity, the participants' knowledge and understanding of rabbit farming increased. Conclusion: The implementation of community service activities as a whole is beneficial to the community and LMDH Wana Karya Lestari. Therefore, it is expected to be carried out sustainably.